Fc-Dependent and Fc-Independent Opsonization of Cryptococcus neoformans by Anticapsular Monoclonal Antibodies: Importance of Epitope Specificity - Netski, Dale (American Society for Microbiology, 2002)
Monoclonal antibodies (MAbs) reactive with glucuronoxylomannan (GXM), the major capsular polysaccharide of the yeast Cryptococcus neoformans, produce distinct capsular reactions when viewed by differential interference contrast microscopy. These reactions depend on the epitope specificity of the antibody. Opsonic activities of immunoglobulin G1 (IgG1) MAbs that produce patterns termed rim and puffy were examined. Rim-pattern MAbs are reactive with an epitope shared by GXM serotypes A, B, C, and D. Puffy-pattern MAbs are reactive only with serotypes A and D. In phagocytosis assays, using serotype A cells and resident murine peritoneal macrophages, rim-pattern MAbs were markedly more opsonic than puffy-pattern MAbs. F(ab′)(2) fragments of rim-pattern MAbs were synergistic with heat-labile factors in normal human serum for opsonization of the yeast. F(ab′)(2) fragments of puffy-pattern MAbs were also synergistic with normal serum in opsonization but at a much lower level than fragments of rim-pattern MAbs. Normal serum alone was not opsonic. F(ab′)(2) fragments of rim-pattern MAbs, but not puffy-pattern MAbs, stimulated phagocytosis of encapsulated cryptococci in the absence of serum. This serum-independent opsonic action of F(ab′)(2) fragments was abrogated by pretreatment of macrophages with purified GXM, suggesting the involvement of a phagocyte GXM receptor. The results indicate that (i) there are multiple mechanisms by which anticapsular IgG MAbs facilitate phagocytosis of encapsulated cryptococci, (ii) some anti-GXM antibodies are opsonic in an Fc-independent manner, and (iii) opsonic activity correlates with the capsular reaction and occurs in an epitope-specific manner.